2021
DOI: 10.1101/2021.03.24.435852
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of transcript enrichment and detection bias in single-nuclei RNA-seq for mapping of distinct human adipocyte lineages

Abstract: Single-cell RNA-sequencing (scRNA-seq) enables molecular characterization of complex biological tissues at high resolution. The requirement of single-cell extraction, however, makes it challenging for profiling tissues such as adipose tissue where collection of intact single adipocytes is complicated by their fragile nature. For such tissues, single-nuclei extraction is often much more efficient and therefore single-nuclei RNA-sequencing (snRNA-seq) presents an alternative to scRNA-seq. However, nuclear transc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…1 a , top ), which is consistent with previous studies of UMI-based protocols ( 11 ). On the other hand, unspliced mRNA counts strongly correlate with gene length ( 12 ) ( Fig. 1 a , bottom ).…”
Section: Introductionmentioning
confidence: 98%
“…1 a , top ), which is consistent with previous studies of UMI-based protocols ( 11 ). On the other hand, unspliced mRNA counts strongly correlate with gene length ( 12 ) ( Fig. 1 a , bottom ).…”
Section: Introductionmentioning
confidence: 98%
“…For brown adipogenesis, preadipocytes showed heterogeneity at day 0 (Preadipocyte-1 and Preadipocyte-2, Fig. S1B), with the Preadipocyte-2 population expressing genes that correspond to adipogenic capacity (Gupta et al 2021). Independent analysis of brown nuclei harvested at later time-points (day-5 to day-20) showed similar preadipocyte heterogeneity along with capture and detection of mature adipocytes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Preadipocytes from both lineages were isolated and then immortalized to allow for long-term in vitro cell-culture. Previously reported data demonstrated highly concordant molecular features between primary and immortalized preadipocytes (Gupta et al 2021), and in vitro differentiated adipocytes were shown to recover gene expression profiles and function of primary human neck BAT and WAT (Xue et al 2015).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…So far, the lower-dimensional latent representations learned by scVI have primarily been used to correct for batch effects, i.e., systematic differences between, e.g., well plates during the execution of an experiment, and to integrate biological data from different modalities. For example, Gupta et al (2021) investigated single-nuclei RNA-sequencing (snRNA-seq) for its ability to identify cell types at different states of adipogenesis. They used scVI for removing technical batch effects which facilitated integrating snRNA-seq and scRNA-seq data for inferring joint patterns between both data types.…”
Section: Single Cell Variational Inference (Scvi)mentioning
confidence: 99%